2015
DOI: 10.1177/1362361315589477
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in metacognitive monitoring in mathematics assessments in learners with autism spectrum disorder

Abstract: Children and adults with autism spectrum disorder have been found to have deficits in metacognition that could impact upon their learning. This study explored metacognitive monitoring in 28 (23 males and 5 females) participants with autism spectrum disorder and 56 (16 males and 40 females) typically developing controls who were being educated at the same level. Participants were asked a series of mathematics questions. Based upon previous research, after each question they were asked two metacognitive question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 64 publications
2
28
1
Order By: Relevance
“…For instance, probing metamemory from what participants remember of a video about kangaroos, Grainger et al [] found that although both individuals with ASD and TD individuals were able to use the judgment of confidence scale appropriately, where both TD participants and participants with ASD gave higher confidence ratings for easy questions compared to impossible questions, there were significant differences between groups in the confidence ratings for correct and incorrect answers, which are in line with our findings. Similarly, Brosnan et al [] found similar math performance but different awareness of errors in individuals with ASD, which also match our findings of similar first‐order task performance but differential error‐monitoring abilities in individuals with ASD. Nonetheless, it should be noted that a nonsignificant trend emerged in the temporal error‐monitoring of individuals with ASD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, probing metamemory from what participants remember of a video about kangaroos, Grainger et al [] found that although both individuals with ASD and TD individuals were able to use the judgment of confidence scale appropriately, where both TD participants and participants with ASD gave higher confidence ratings for easy questions compared to impossible questions, there were significant differences between groups in the confidence ratings for correct and incorrect answers, which are in line with our findings. Similarly, Brosnan et al [] found similar math performance but different awareness of errors in individuals with ASD, which also match our findings of similar first‐order task performance but differential error‐monitoring abilities in individuals with ASD. Nonetheless, it should be noted that a nonsignificant trend emerged in the temporal error‐monitoring of individuals with ASD.…”
Section: Discussionsupporting
confidence: 91%
“…In neither the perceptual decision making nor the interval timing task and unlike the TD children, did the confidence ratings of children with ASD match their objective performance. This is in line with Sokhadze et al [2010]'s brain response findings that suggest individuals with ASD to have disrupted neural processing of errors as well as with behavioral findings [Grainger et al, 2016;Brosnan et al, 2016]. For instance, probing metamemory from what participants remember of a video about kangaroos, Grainger et al [2016] found that although both individuals with ASD and TD individuals were able to use the judgment of confidence scale appropriately, where both TD participants and participants with ASD gave higher confidence ratings for easy questions compared to impossible questions, there were significant differences between groups in the confidence ratings for correct and incorrect answers, which are in line with our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Metacognitive training is effective in improving children’s EF skills ( Cornoldi et al, 2015 ), including those with ASD ( Grainger et al, 2016 ; Maras et al, 2017 ). Difficulties in metacognitive functions are frequently reported in ASD and can impact a number of areas of competency ( Grainger et al, 2014 ; Brosnan et al, 2016 ; McMahon et al, 2016 ), including social functioning ( Torske et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in standard judgement of confidence (JOC) tasks participants are typically asked to make retrospective judgements assessing how confident they are that their answer to a question is correct. The few existing studies of metacognitive monitoring in ASD have suggested that individuals with this disorder demonstrate diminished accuracy when making both feeling of knowing judgements (Grainger et al 2014 ; Wojcik et al 2013 ) and judgments of confidence (Grainger et al 2016 ; Wilkinson et al 2010 ; Brosnan et al 2015 ; McMahon et al 2016 ; but see Sawyer et al 2014 ). That is, the correspondence between participants’ predictions about their own memory performance and their actual memory performance appears to be lower among individuals with ASD than among neurotypical individuals, when making these types of metacognitive judgments.…”
Section: Introductionmentioning
confidence: 99%